Man Should Rejoice, by Hugh MacLennan : A Critical Edition - MacLennan, Hugh, 1907-1990 (Book collections on Project MUSE., 2019)
"This critical edition of Man Should Rejoice is comprised of a critical introduction, a bibliography of published and unpublished sources, a fully-edited text based on a typescript of the novel from the McGill archives, a list of textual emendations, and explanatory notes that contextualize the novel. The introduction draws upon extensive archival research undertaken in three Canadian archival collections located in Montreal and Calgary and provides relevant historical, cultural, and biographical context for the novel which was completed in 1937 and left unpublished due to economic conditions during the Great Depression. It reconstructs, from hundreds of archival documents, a textual history of the novel's production that acknowledges the crucial contribution of Dorothy Duncan (who heavily revised the text and assisted MacLennan behind the scenes); it explores the critical reception of MacLennan's fiction from the 1930s to the present. "--